Macrothelypteris torresiana (Guad.) Ching (Thelypteridaceae) - A new record for Bangladesh - Mirza, Momtaz Mahal (Bangladesh Journal of Plant Taxonomy, 2006)
Not available. Key words: Macrothelypteris torresiana, New record, Bangladesh DOI: 10.3329/bjpt.v13i1.597 Bangladesh J. Plant Taxon. 13(1): 69-71, 2006 (June)